Excavations at Çatal Hüyük. First Preliminary Report, 1961 - Mellaart, James
Introduction – Summary of the 1961 Campaign – Architecture – Burial Habits – Pottery – Other Industries and Crafts – Economy – Religion – Wall-Paintings.